Investigating the Effect of Liquidity, Leverage, Sales Growth, and Good Corporate Governance on Financial Distress - Agustina Dianova; Joicenda Nahumury (JASF: Journal of Accounting and Strategic Finance, 2019)
Large companies may experience financial distress because of their inability to compete. Therefore, investors should be more vigilant in investing their funds. Some ways that can be done is through cash flow analysis, analysis of corporate strategy, and analysis of financial statements. This study aims to determine the effect of liquidity, leverage, sales growth, and good corporate governance on financial distress. The study used 55 samples of telecommunication and non-construction companies listed in Indonesia Stock Exchange period 2013-2017. The technique sampling in this study is the purposive sampling method. The data analysis method is PLS (Partial Least Square). The results of this study indicate that liquidity, leverage, sales growth, and good corporate governance do not affect financial distress. These unexpected results may due to the limitation of this study. Therefore, for future research in financial distress, it is suggested to take into account the sample size and other variables that expected to affect financial distress.